The marginal product of capital: a persistent international puzzle - Robert S. Chirinko; Debdulal Mallick (Center for Economic Studies and ifo Institute (CESifo), 2008)
Large and sustained differences in marginal products of capital (MPKs) across countries are sharply at odds with the core implications of the neoclassical framework. Lucas (1990) and many subsequent studies have examined reasons for this MPK differential. In a recent contribution, Caselli and Feyrer (2007) take the ground out from under this debate by reconsidering measurement issues and concluding that the MPK differential vanishes. Despite Caselli and Feyrer's important advances in measurement, the international MPK puzzle persists. We show that the measurement of MPKs in their framework is substantially affected by adjustment costs in the accumulation of capital. With the proper technology and a plausible parameterization of adjustment costs, the MPK in poor countries is much higher than the MPK in rich countries. Why capital flows do not eliminate the MPK differential remains a persistent international puzzle. We examine the quantitative importance of financial frictions, relative prices, and adjustment costs in accounting for the MPK differential and document that adjustment costs provide the leading explanation.
Keywords: O11; O16; E22; 330; Marginal product of capital; adjustment costs; macroeconomic analysis of economic development; international capital flows; Marginalanalyse; Kapital; Vergleich; Entwicklung; Investition; Anpassungskosten; Internationale Kapitalmobilität; Welt